Depositional palaeoenvironments in a tide-influenced delta plain with amphibian and Cycadophyta remains - the Triassic Zarzaitine Formation (Algerian eastern Sahara) - Mazrou, S.; Lasnami, Y.; Amer, J.; Boutaleb, A. (Geologos, 2024)
In the region of In Amenas (south-eastern Algeria) Triassic deposits crop out, on top of Palaeozoic rocks under an angular unconformity. A study of their sedimentological and palaeoenvironmental characteristics has revealed a sandy-clay unit with vertebrate remains, tree trunks and ichnofossils of Middle-Late Triassic age. This so-called Zarzaitine Formation, which reflects deposition in a deltaic environment, shows three facies associations. The first defines an upper and shallow intertidal mixed flat zone with in-situ temnospondyl capitosauroid remains, associated with Skolithos ichnofacies, while the second one defines a lower intertidal delta plain zone, composed of sandstone, distributary channels and muddy interdistributary areas,which record daily tidal rhythmites and monthly tidal bundles. The third, and last, facies association represents an upper delta plain of the supratidal zone, characterised by coarse sandstone deposits of braided rivers and a Cycadophyta palaeosol. Previous work, which led to considering these Triassic deposits as a series composed of four formations, deposited in a braided rivers environment, whose lower floodplains constituted ecological niche for a temnospondyl fauna, under hot and dry climatic conditions and plants belonging to this same formation, for mushrooms and algae, will also be considered.